Scleromyositis: A distinct novel entity within the systemic sclerosis and autoimmune myositis spectrum. Implications for care and pathogenesis - Giannini, Margherita; Ellezam, Benjamin; Leclair, Valérie; Lefebvre, Frédéric; Troyanov, Yves; Hudson, Marie; Senécal, Jean-Luc; Geny, Bernard; Landon-Cardinal, Océane; Meyer, Alain (Frontiers in Immunology, 2023)
Systemic sclerosis and myositis are both associated with a decreased quality of life and increased mortality. However, the prognosis and care largely depend on the subtypes of these diseases. Indeed, systemic sclerosis is a heterogeneous disease, the two predominant forms of the disease being limited and diffuse scleroderma. Myositis is also a heterogeneous group of autoimmune myopathies that classically encompass necrotizing myopathy, antisynthetase syndrome, dermatomyositis and inclusion body myositis. Recent data revealed that an additional disease subgroup should be recognized within both the systemic sclerosis and the myositis spectra that has been denominated “scleromyositis”. This concept is supported by recent clinical, immunological and histopathological findings that have important implications for patient management and better understanding of the disease pathophysiology. As compared with other types of systemic sclerosis and myositis, scleromyositis patients clinically present with a peculiar muscle involvement (i.e. distribution of muscle weakness) along with systemic involvements (i.e. extra-muscular complications), some of which are associated with a poor prognosis. Moreover, several autoantibodies have been specifically associated with this disease. Importantly, these autoantibodies are not currently taken into account by current diagnosis and classification criteria for systemic sclerosis and myositis. Finally, some histopathological muscle lesions have been shown to be hallmarks of scleromyositis, bringing new insights into the pathogenesis of this disease, and helping the diagnosis, especially when no autoantibodies are present (“seronegative” scleromyositis). No consensual guidelines are available for the management of these patients but recent data are paving the way toward a new therapeutic approach dedicated to these patients.